Placement Pattern of Polri Human Resources for Overseas Graduates - Muhamad Kevin Ramadhan; Chrysnanda Dwilaksana; Payaman Jan Simanjuntak (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is motivated by the Police HR placement issue who receive LPDP Scholarship studying abroad incorrectly according to the scientific field that has been taken, which has an impact on the discrepancy between competence and work demands in the field, which can cause insecure in the HR individual and potentially unprofessionalism of work in the field. Therefore, this research aimed at analyzing the pattern of placement of the National Police's human resources who graduated from abroad. This is qualitative research with a field research approach, with data collection techniques carried out through interviews, observation and document study which were then analyzed using data reduction methods, data presentation, and data verification. The findings indicate that the placement pattern for Polri HR of overseas graduates is carried out in accordance with Perkap Polri No. 9 of 2016 concerning the Development System for Police Members. However, in practice there are problems of violations of the principles of justice experienced by the Polri human resources, which have an impact on violations of principles, which can lead to members' retaliatory attitudes which in turn cause delays in the achievement of organizational goals.